PERANCANGAN ULANG ANTARMUKA WEBSITE SD ISLAM HARAPAN IBU PONDOK PINANG BERBASIS IDENTITAS VISUAL DAN PRINSIP DESAIN RAMAH PENGGUNA - Benny Muhdaliha; Yori Pusparani; Fachri Febriyasa (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
The rapid development of digital technology requires educational institutions to provide information platforms that are accessible, effective, and visually representative of their institutional identity. SD Islam Harapan Ibu Pondok Pinang, as a modern Islamic elementary school, requires a redesigned website interface that not only delivers information clearly but also reflects Islamic values and a child friendly educational approach. This study aims to develop a website interface that is visually appealing, informative, and easy to use, particularly for parents and prospective students. The research employs data collection through content observation, user needs analysis, wireframe sketching, and the selection of visual elements such as color schemes, typography, iconography, and responsive layout structures. The findings indicate that an interface emphasizing simplicity, clarity of information, and visual consistency with the school’s identity enhances readability, user experience, and public perception of the school’s professionalism. The originality of this study lies in its integration of Islamic values and child-friendly design principles into the development of a school website interface an approach that remains underexplored within the context of Islamic elementary education. The implications of this research highlight the importance of interface designs that are not only functional but also visually communicative in strengthening the school’s digital communication strategy and supporting institutional promotion in the digital era.